Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Pegawai - Nurita Indriastuti (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACT This study aims is to determine the influence of organizational culture on employee performance, knowing the work motivation on employee performance and to determine the influence of organizational culture and work motivation on the performance of employeess in the Korem 072/Pamungkas Yogyakarta. The method in this research using survey method, data collection technique used is the primary data collection technique with the entire population of the corps of 52 employees. Data analysis using multiple linear regression analysis. From the analysis results it is known that organizational culture has an influence on the performance of employees in the environment Korem 072/Pamungkas, this evidence is seen from the value of t on the coefficient on the results of regression analysis where the value of t equal to 3,623 with a sinificant level of 0,001. From the analysis results it is known that work motivation has an influence on the performance of employees in the environment Korem 072/Pamungkas, this evidence is seen from the value of t on the coefficient on the results of regression analysis where the value of t equal to 3,187 with a sinificant level of 0,003. From the analysis result obtained fvalue count of 24,198 with the significance value (p) 0,000 means the significance (p) < 0,05 then it can be said that simultaneously variable organizational culture dan work motivation have a significant influence on employee performance in the environment Korem 072/Pamungkas Yogyakarta.